Effectiveness of Home-Based Physical Exercise for The Elderly: Endurance and Its Impact on Mobility and Functional Activities - Meisya Azalia Putri; Noviana, Mita (Universitas Airlangga, 2026)
Background: Aging leads to decreased mobility and functional activity due to reduced muscle strength, balance, and endurance. Home exercise is a promising intervention to mitigate this decline. However, the role of endurance as a mediator in enhancing mobility has yet to be explored. Objective: This study analyzes the effectiveness of home physical exercise in improving mobility and functional activity in older adults, emphasizing endurance as a mediating factor. Methods: A systematic literature review (SLR) based on PRISMA guidelines was conducted, analyzing 116 relevant articles from academic databases. Studies were screened and selected based on inclusion and exclusion criteria, ensuring methodological rigor and relevance to the research topic. Results & Discussion: Findings indicate that home exercise significantly improves endurance, which, in turn, enhances mobility and functional performance. Increased endurance contributes to better movement efficiency, postural stability, reduced fatigue, and independence in daily activities. Key factors influencing the effectiveness of home exercise include the intensity and frequency of workouts, adherence, social support, underlying health conditions, and implementation methods. Despite its benefits, challenges such as physical limitations, lack of motivation, and environmental constraints hinder the sustainability of home exercise programs. Conclusion: Home exercise is an effective strategy for improving mobility in older adults, with endurance playing a crucial mediating role. Future interventions should focus on personalized exercise programs, social support, and technology integration to enhance adherence and maximize benefits.